General anesthesia versus spinal anesthesia length of stay comparison for elderly patients recovering from surgery - Resiana Karnina; Aquita Tiara Melati Cahyani; Justika Usmadhani Aulya; Mutia Hayu (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Introduction: The commonly used types of anesthesia are general anesthesia and spinal anesthesia. Elderly patients heal more slowly due to weakened immune systems and decreased organ function. The purpose of this study was to investigate the length of hospital stay among elderly patients after surgery by comparing two types of anesthesia: general and spinal. Methods: This is a cross-sectional study involving a geriatric population aged 60 years and older who underwent surgery under spinal or general anesthesia between January and June 2024 at a public hospital in East Jakarta. A total of 107 samples met the criteria. The independent variables were general anesthesia and spinal anesthesia, and the dependent variable was the length of stay (LOS) after surgery. The bivariate study employed Chi-square analysis, using a p-value of 0.05 as the criterion for significance. Results: There was no statistically significant difference in LOS between the two anesthetics (p-value = 0.24). We analyzed four variables using ordinal regression to examine their effect on anesthesia type and LOS. The gender category was obtained with (b = 0.045, p-value = 0.93), the age category with (b = -0.126, p-value = 0.83), the body mass index category with (b = -0.429, p-value = 0.41), and the comorbid category with (b = -0.137, p-value = 0.68). None of these variables showed any effect on the relationship between anesthesia type and length of hospital stay. Conclusion: The study found that the length of stay for elderly patients after recovering from surgery was not statistically significant, regardless of the type of anesthesia used, including both general and spinal anesthesia.